2001
DOI: 10.1038/sj.cr.7290088
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel gene (C17orf25) from the deletion region on chromosome 17p13.3 in hepatocelular carcinoma

Abstract: Using a combination of hybridization of PAC to a cDNA library and RACE technique, we isolated a novel cDNA, designated as C17orf25 (Chromosome 17 open reading frame 25, previously named it HC71A), from the deletion region on chromosome 17p13.3. The cDNA encodes a protein of 313 amino acids with a calculated molecular mass of 34.8 kDa. C17orf25 is divided into 10 exons and 9 introns, spanning 23 kb of genomic DNA. Northern blot analysis showed that the mRNA expression of C17orf25 was decreased in hepatocellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…Report construct and mutagenesis by the bridgingbased two round-PCR method A 2.1 Kb genomic fragment containing the 5'-flanking region of RNMTL1 was subcloned from PAC579, a bacteriophage P1-derived artificial chromosomal vector based construct containing 116 kb insert [7,9]. Sequencing of both strand of this fragment using vector-specific primers revealed that it contained about 1.5 Kb of the 5 -flanking region of RNMTL1 as well as the translation start codon.…”
Section: Rna Preparation and Expression Profiling By A Semi-quantitatmentioning
confidence: 99%
See 1 more Smart Citation
“…Report construct and mutagenesis by the bridgingbased two round-PCR method A 2.1 Kb genomic fragment containing the 5'-flanking region of RNMTL1 was subcloned from PAC579, a bacteriophage P1-derived artificial chromosomal vector based construct containing 116 kb insert [7,9]. Sequencing of both strand of this fragment using vector-specific primers revealed that it contained about 1.5 Kb of the 5 -flanking region of RNMTL1 as well as the translation start codon.…”
Section: Rna Preparation and Expression Profiling By A Semi-quantitatmentioning
confidence: 99%
“…In our previous efforts to identify within 17p13.3 the vital genes, functions of which is to prevent the malignant transformation of the hepatocyte, a 116 Kb fragment carried by a PAC clone, PAC579, has been fully sequenced and thirteen genes have been cloned by screening the liver cDNA library with the unique sequence within this fragment as probe and gene-mining bioinformatically [6][7][8][9]. Purely on the basis of its sequence similarity to a family of the genes well conserved in evolution and encoding the proteins capable of methylating the ribosomal RNA, the gene studied in this report is annotated as the human RNA methyltransferase like 1 ( RNMTL1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the LOH region within chromosome 17p13. 3 in human HCC in China, and some HCC related genes have been identified from this region [9][10][11]. Identification of novel molecules that regulate HCC cell proliferation could improve our understanding of the regulatory networks and lead to novel diagnosis and treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…AF177342) is one of thirteen genes cloned from a region displaying a high score of loss of heterozygosity within chromosome 17p13.3 in human hepatocellular carcinoma in China [1]. To unveil the underlying mechanisms for the transcription regulation of this gene and understand its implication to the hepatocellular carcinogenesis, we looked into the relevant aspects by both bioinformatic and experimental executions.…”
Section: Introductionmentioning
confidence: 99%